2020
DOI: 10.3390/ma13245607
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural, Mechanical, Corrosion and Cytotoxicity Characterization of Porous Ti-Si Alloys with Pore-Forming Agent

Abstract: Titanium and its alloys belong to the group of materials used in implantology due to their biocompatibility, outstanding corrosion resistance and good mechanical properties. However, the value of Young’s modulus is too high in comparison with the human bone, which could result in the failure of implants. This problem can be overcome by creating pores in the materials, which, moreover, improves the osseointegration. Therefore, TiSi2 and TiSi2 with 20 wt.% of the pore-forming agent (PA) were prepared by reactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Many studies have successfully shown that coated screws may significantly increase resistance against pull-out force in comparison to uncoated screws [ 80 , 81 , 82 ]. Regarding potential toxicity associated with the leaching of the vanadium and aluminum ions from the Ti-6Al-4V implants, the amount of these metals released is minimal and does not induce suspected health problems, such as neurological or enzymatic disorders [ 83 ].…”
Section: Mechanical Characteristics Of the Most Frequently Used Metal...mentioning
confidence: 99%
See 3 more Smart Citations
“…Many studies have successfully shown that coated screws may significantly increase resistance against pull-out force in comparison to uncoated screws [ 80 , 81 , 82 ]. Regarding potential toxicity associated with the leaching of the vanadium and aluminum ions from the Ti-6Al-4V implants, the amount of these metals released is minimal and does not induce suspected health problems, such as neurological or enzymatic disorders [ 83 ].…”
Section: Mechanical Characteristics Of the Most Frequently Used Metal...mentioning
confidence: 99%
“…Decreasing Young’s modulus of titanium alloys may be also achieved by creating pores in them. A biomechanical study by Skolakova et al [ 83 ] has shown that Ti alloy with the addition of 30 wt.% pore-forming agent (PA) obtained with self-propagating high-temperature synthesis (SHS) exhibits a very similar elastic modulus (~9 GPa) to human bone with good corrosion resistance. However, mechanical strength decreased after the SHS procedure and further studies are necessary to evaluate the usefulness of Ti with 30 wt.% PA in LIF.…”
Section: Mechanical Characteristics Of the Most Frequently Used Metal...mentioning
confidence: 99%
See 2 more Smart Citations
“…However, the implant of a completely compact, hard, artificial bone shows homogeneous behavior after surgery. When subjected to external load, the dense and hard bone implant bears more stress, which reduces the load transferred to the host bone, resulting in a change in the stress environment of the host bone, which is called a stress shielding phenomenon [ 4 ]. When stress shielding occurs in the bone tissue, the stress level on the bone is at a low level for a long time, which causes the bone tissue to gradually absorb, causing osteoporosis around the bone prosthesis and the loosening of the implant, leading to the patient’s pain [ 5 ].…”
Section: Introductionmentioning
confidence: 99%